2011
DOI: 10.3174/ajnr.a2551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lens-Induced Myopia on Visual Cortex Activity: A Functional MR Imaging Study

Abstract: BACKGROUND AND PURPOSE:Myopia is a type of refractive error that blurs retinal image and in turn can change neural signals transferred from retina to visual cortex. The purpose of this study was to evaluate the effect of induced myopia on occipital visual cortex activity by fMRI results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…We found that V1 activity was strongly affected by refractive errors, which was congruent with the findings of previous fMRI studies showing myopia-induced reductions in BOLD signals in and around V1 [ 11 , 12 ]. In these studies, the extent of the V1 activity reduction was approximately 20 % by a +8D lens [ 12 ] and 10 % by +1D lens [ 11 ], which was slightly smaller than the value obtained in the present study (25 % by +1D). This may have been due to differences in the methodology used, namely, a VEF component is more sensitive to synchrony in neuronal firing than BOLD changes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that V1 activity was strongly affected by refractive errors, which was congruent with the findings of previous fMRI studies showing myopia-induced reductions in BOLD signals in and around V1 [ 11 , 12 ]. In these studies, the extent of the V1 activity reduction was approximately 20 % by a +8D lens [ 12 ] and 10 % by +1D lens [ 11 ], which was slightly smaller than the value obtained in the present study (25 % by +1D). This may have been due to differences in the methodology used, namely, a VEF component is more sensitive to synchrony in neuronal firing than BOLD changes.…”
Section: Discussionsupporting
confidence: 92%
“…We herein described one of these experiments using transient VEFs. Although two fMRI studies previously demonstrated that induced myopia reduced visual evoked cortical activity in Brodmann’a areas 17 and 18 [ 11 ] or in V1 and V2 [ 12 ], there is currently no electrophysiological study that describes neural origins of refraction-sensitive activity. We employed a low-luminance simple grating in the present study instead of a pattern reversal stimulus in order to reduce the overall luminance of the stimulus by considering subject discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be the end result of decreased retinal ganglion cells or caused by decreased integrity of the optic radiations, or a combination of both of these factors. Other studies have demonstrated decreased visual cortical activation due to anterior pathway lesions, including that due to lens abnormalities 30 and glaucoma, 31 as well as in binocular rivalry. 32 Decreased visual cortical activation in lens-induced myopia is of considerable practical importance in clinical task-based MRI studies and highlights the need to correct this before the study being performed.…”
Section: Discussionmentioning
confidence: 93%
“…32 Decreased visual cortical activation in lens-induced myopia is of considerable practical importance in clinical task-based MRI studies and highlights the need to correct this before the study being performed. 30 Many factors have been investigated in predicting visual recovery after optic chiasm decompression surgery. Reduced RNFL thickness, which reflects irreversible damage to retinal ganglion cells, has been demonstrated to be a reliable predictor of poor visual recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using fMRI showed that lens-induced myopia reduces activity in the visual cortex. 23 That added to the evidence already given by visual evoked potentials that amplitude in reduced and latency is increased in myopia. 24,25 Based on previous findings, we would predict that myopes might need longer temporal integration than emmetropes at the periphery of the retina.…”
Section: Introductionmentioning
confidence: 99%